THE FOURTH INDUSTRIAL REVOLUTION: CHALLENGES FOR DEVELOPING COUNTRIES STRATEGIC LEADERSHIP - Tsetsegmaa.Ts; Stephen Duggan (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
skills development is increasingly the focus of investments in the education sector. Historically, ODA for education sector development focused on Basic Education (Grades K-9). Since 2005, there has been a shift in ODA thinking with a focus on capacity development and workforce development as underpinning support for economic development. Official development assistance is defined as government aid designed to promote the economic development and welfare of developing countries. Development assistance may be provided bilaterally, from donor to recipient, or channelled through a multilateral development agency such as the United Nations or World Bank. Skills development makes a logical fit as the benefits concern economic development and citizen welfare. Skills development programs make sense to donors as it breaks down barriers of separate sectors and enables bilateral and multilateral agencies to have a lens for financing education as an intersectoral investment with many benefitting government Ministries. Mongolia has long benefitted from ODA and education sector support has been a strong focus. Around 2008, both donors and the private sector examined provisions for technical and vocational education and training (TVET) and concluded that if Mongolia was going to experience sustained economic growth, chronic skill shortages needed to be addressed. The Asian Development Bank (ADB) quickly grasped the importance of skills development and soon measures were in place for a comprehensive program in skills development for employment covering priority economic sectors and industries. This paper examines prospects for knowledge and skills development in Mongolia’s higher education sector. It will ask what needs to take place for universities to develop advanced skills and in nurturing innovation and entrepreneurship utilizing transformative technologies like cloud computing, internet of things (IoT), machine learning, and robotics. The paper explores what universities will need to do to convince faculty of the importance of increasing university graduate employability. This involves upskilling to meet new labour market demands, and increasing employability of both undergraduates and postgraduates to ensure equitable development. There is also scope for exploring means for strengthening innovation capacity.